Two new species of eriophyoid mites (Acari: Prostigmata: Eriophyoidea) associated with Callerya Endl. and supplementary descriptions of Fujianacarus wisterianis from China - Ruan, Hong-Yan; Shou, Ru-Fang; Lian, Ran-Ran; Tan, Meng-Chao (Zootaxa, 2023)
Two new eriophyid mite species (Acari: Prostigmata: Eriophyoidea) were described from the host plants of the genus Callerya Endl. during a field survey in China: Tetra nitidae sp. nov. vagrant on leaves of Callerya nitida (Bentham) R. Geesink (Leguminosae), and Calepitrimerus calleryus sp. nov. vagrant on leaves of Callerya tsui (F. P. Metcalf) Z. Wei & Pedley. Both species caused no apparent symptoms in their host plants. Additionally, this paper provides a supplementary morphological description and illustrations of Fujianacarus wisterianis Song, Xue & Hong, 2008 (Eriophyoidea).